Nalar Hukum Progresif Hakim Agama: Implementasi Hak Ex-Officio Dalam Putusan Perceraian di Pengadilan Agama Tulungagung - Khaidarulloh, Khaidarulloh; Maratus, Nuril Farida; Aulia, Sidiq (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Progressive legal reasoning of Islamic judges, especially regarding Ex-Officio rights, is a significant issue in this research. This article discusses the development and actualization of the Ex-Officio rights of Islamic judges in the decisions of Islamic family law in the Religious Court of Tulungagung from 2014 to 2020. Through a literature analysis and empirical data, this research describes the changes and developments in the application of Ex-Officio rights by Islamic judges in the context of divorce cases. As a result, judges can use ex officio rights to make broader decisions than those presented in the application, such as determining maintenance for parties who did not file the application. This broadens the scope of court decisions and provides more effective legal protection to those affected by divorce. Additionally, ex officio rights serve as a legal protection tool for women in divorce cases. Judges can issue decisions to prevent women from facing economic or social losses after divorce and ensure the full respect of women's rights.